The Relationship Between Salted Fish Consumption Habits and the Incidence of Hypertension During Pregnancy in the Coastal Areas of Tuban Regency - Utami, Sri; Budi Prasetyo; Ivon Diah Wittiarika (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Hypertension during pregnancy is a significant health issue and one of the leading causes of morbidity and mortality among pregnant women worldwide, with higher prevalence in regions of high sodium intake. In Indonesia, hypertension during pregnancy poses serious challenges, especially in coastal areas where salted fish is a common dietary staple. Salted fish, preserved through processes that increase sodium levels, can raise blood pressure when consumed excessively, elevating the risk of hypertension in pregnant women. This study examines the relationship between salted fish consumption habits and the incidence of hypertension during pregnancy in coastal regions of Tuban. The research employed an observational analytic method with a cross-sectional design. Data were collected from 99 pregnant women attending antenatal care (ANC) visits at several coastal community health centers, using consecutive sampling conducted from July 29 to August 16, 2024. Information was gathered through questionnaires and medical records. The independent variable in this study was the habit of consuming salted fish, while the dependent variable was the incidence of hypertension during pregnancy. Data were analyzed using Fisher's Exact test with a significance level of α=0.05. The results showed a p-value of 0.000, indicating a statistically significant relationship between salted fish consumption and hypertension in pregnancy. The findings demonstrate that more frequent consumption of salted fish correlates with a higher risk of developing hypertension during pregnancy. These results highlight the need for dietary management, particularly in coastal communities, to reduce sodium intake and lower the risk of hypertension, ultimately improving maternal health outcomes.